Change from lung adenocarcinoma to small cell lung cancer as a mechanism of resistance to afatinib - Manca, Paolo (Oncotarget, 2017)
We report the case of a patient affected by advanced EGFR mutation-positive lung who experienced resistance to therapy during treatment with Afatinib through the occurrence of a switch of tumor histotype to small cell lung cancer (SCLC) with features of a G3 neuroendocrine carcinoma. Unexpectedly, the switch to SCLC histotype occurred in the only site not responsive to afatinib and subsequently the most responsive to chemotherapy. Our case shows that occurrence of switch to SCLC is a possible mechanism of resistance during treatment with Afatinib.